A systematic review of the intrapersonal correlates of motivational climate perceptions in sport and physical activity. (May 2015) - Harwood, Chris G.; Keegan, Richard J.; Smith, Jonathan M.J.; Raine, Adam S.
Abstract: Objectives: The purpose of this study was to systematically review and appraise the achievement goal literature (1990–2014) with a view to identifying the intra-individual correlates of motivational climate perceptions, and to identify research gaps and avenues in need for further development. Design: Systematic review. Method: Four databases were searched, leading to 104 published studies being sampled (121 independent samples) that met inclusion criteria. Correlates were grouped into 17 categories and qualitative analysis focussed on identifying the associations predicted by achievement goal theory. Effect sizes were calculated using the Hunter-Schmidt method for correcting sampling error. Results: A total population size of 34, 156 ( χ  = 316.3, σ  = 268.1) was sampled in the analysis, with the published mean ages ranging from 10.0 to 38.2 years ( χ  = 16.5 years, σ  = 4.7). Perceptions of a task or mastery climate were consistently associated with a range of adaptive motivational outcomes including perceived competence, self-esteem, objective performance, intrinsic forms of motivational regulation, affective states, practice and competitive strategies and moral attitudes, and the experience of flow. Perceptions of an ego or performance climate were positively associated with extrinsic regulation and amotivation, negative affect, maladaptive strategy use, antisocial moral attitudes and perfectionism, but negatively associated to positive affect and feelings of autonomy and relatedness. Conclusions: After reviewing the sum total of research in this topic area, the authors appraise the options for future research to make meaningful progress in developing understanding of the social determination of motivation in sport and physical activity settings. Highlights: Intrapersonal correlates of perceived motivational climate were systematically reviewed. Perceived task/mastery climate related to adaptive correlates; perceived ego/performance climate related to maladaptive correlates. A small age range and a lack of focus on behavioural correlates was noted in existing work. Individual sports, parents and peers received limited attention in research studies. More innovative research approaches and new measures are recommended for this area.